USE VLSM (VARIABLE LENGTH SUBNET MASKING) ANDROID BASED SIMULATOR FOR ADMINISTRATIVE SUPPORT NETWORK - Aji, Bimio Wahyu; Wintolo, Hero; Nugraheny, Dwi (Compiler, 2013)
Administration o f networking IP addressing especially IP version 4 have a less using IP address for the limited. Through for the using by networking o f services base on TCP/IP addressing, however that can be used VLSM (Variable Length Subnet Masking) method o f subnetting addressing thorough the public area networking to divided IP addressing private it's called as sub network ID or Local Area Network (IP private). Therefore dividing have choose a calculate IP addressing o f VLSM Method used by simulator calculating IP address subnetting. The use o f goal-based subnetting android simulator to facilitate the distribution o f IP within the network administrator by using the simulator VLSM IP subnetting calculations automatically and efficiently. An application that helps administrators in calculating VLSM subnetting IP, to support network administration so that administrators can make solving the network ID into sub-networks. IP results obtained from the simulator, can be tested with VLSM on various internet network service providers obtain a quite optimal for purposes o f network administration.